Valid and reliable instrument for measuring Malaysian talented students’ social support - Tuan Zahrah Tuan Mat; Khairul Farhah Khairuddin; Wan Ahmad Munsif Wan Pa; Nur Choiro Siregar (Intelektual Pustaka Media Utama, 2026)
Social support is an essential protective factor against the risk of talent development failure, especially in the catastrophic situation. This study aimed to test the validity and reliability of social support instruments specifically for talented sports students in Malaysia. Content validity index (CVI), exploratory factor analysis (EFA), and internal consistency are the methods used to ensure that measurement instruments are appropriate for use in local contexts and cultures. A total of 268 form four talented sports students aged 16 years were selected by proportionate stratified random sampling in this study. The study found that the instrument had good content validity, with the items reaching the minimum level of CVI value and exceeding the recommended cut-off point of 0.78. Factor analysis found that the final measurement model has three factors, namely i) family support, ii) friends support, and iii) coach support, with factor loading ranging between 0.49 and 0.89. Correlation matrix was also measured through the KMO and Bartlett test of sphericity. All three factors had internal consistency values of 0.83 for coach support and 0.85 for family and friend support, which was defined good. Future research is warranted to explore the instrument with different samples and measurement in various scenarios.